Initiation and long‐term use of benzodiazepines and Z‐drugs in bipolar disorder. (16th February 2018) - Wingård, Louise; Taipale, Heidi; Reutfors, Johan; Westerlund, Anna; Bodén, Robert; Tiihonen, Jari; Tanskanen, Antti; Andersen, Morten
Abstract : Objectives: Increasing evidence points to the harmful effects of long‐term benzodiazepine treatment. Our objective was to study the incidence of, and predictors for, long‐term use of benzodiazepines and Z‐drugs in bipolar disorder. Methods: We conducted a population‐based cohort study, using data from Swedish national registers. Swedish residents aged 18‐75 years with a recorded diagnosis of bipolar disorder or mania between July 2006 and December 2012, and no history of benzodiazepine/Z‐drug use in the past year, were included. Patients were followed for 1 year with regard to prescription fills of benzodiazepines/Z‐drugs. Initiators were followed for another year during which continuous use for >6 months was defined as "long‐term". Patient and prescription characteristics were investigated as potential predictors for long‐term use in multivariate logistic regression models. Results: Out of the 21 883 patients included, 29% started benzodiazepine/Z‐drug treatment, of whom one in five became long‐term users. Patients who were prescribed clonazepam or alprazolam had high odds for subsequent long‐term use (adjusted odds ratios [aORs] 3.78 [95% confidence interval (CI) 2.24‐6.38] and 2.03 [95% CI 1.30‐3.18], respectively), compared to those prescribed diazepam. Polytherapy with benzodiazepines/Z‐drugs also predicted long‐term use (aOR 2.46, 95% CI 1.79‐3.38), as did age ≥60 years (aOR 1.93, 95% CI 1.46‐2.53, compared to age <30 years), and concomitant treatment with psychostimulants (aOR 1.78, 95% CI 1.33‐2.39). Conclusions: The incidence of subsequent long‐term use among bipolar benzodiazepine initiators is high. Patients on clonazepam, alprazolam or benzodiazepine/Z‐drug polytherapy have the highest risk of becoming long‐term users, suggesting that these treatments should be used restrictively.